Pendidikan Kesehatan tentang Terapi Komplementer pada Masa Nifas - Fatihatul Hayati (Jurnal Abdimas Kesehatan (JAK), 2022)
Complementary midwifery services are part of the application of complementary and alternative medicine in midwifery services. Complementary midwifery services are an option for midwives and women to reduce medical interventions during pregnancy and childbirth and the puerperium, and based on experience this is quite helpful. However, most of these therapies are not considered meaningful in conventional medicine. This is due to the scarcity of published clinical evidence and information regarding the effectiveness of complementary obstetric services in pregnancy, childbirth and the puerperium. The use of complementary therapies in the field of midwifery must be proven safe by research. Although traditional / complementary medicine is relatively safer, it does not mean that it does not pose a risk, for that mothers must have adequate knowledge about the use of safe complementary therapies during the postpartum period. This community service is carried out in the work area of the Putri Ayu Community Health Center with the largest target number of pregnant women, so it is hoped that the mother will get correct information about the use of complementary therapies during the postpartum period since pregnancy, so that mothers can leave harmful therapies and utilize complementary therapies appropriately.